Effects of CD20 antibodies and kinase inhibitors on B‐cell receptor signalling and survival of chronic lymphocytic leukaemia cells. (20th November 2020) - Cavallini, Chiara; Galasso, Marilisa; Pozza, Elisa Dalla; Chignola, Roberto; Lovato, Ornella; Dando, Ilaria; Romanelli, Maria G.; Krampera, Mauro; Pizzolo, Giovanni; Donadelli, Massimo; Scupoli, Maria T.
Summary: Recently, clinical trial results have established inhibitors of B‐cell receptor (BCR)‐associated kinase (BAKi), with or without CD20 moniclonal antibodies (mAbs), as the preferred first‐line treatment for most chronic lymphocytic leukaemia (CLL) patients. Using phosphospecific flow cytometry, we showed that in leukaemic cells from CLL patients the CD20 therapeutic antibodies — rituximab, ofatumumab, and obinutuzumab — inhibited BCR signalling pathways targeting preferentially pBTK Y551 — but not BTK Y223 — and pAKT. On the contrary, ibrutinib and idelalisib reduced pBTK Y223 to a higher extent than pBTK Y551 . The strong reduction of pAKT induced by idelalisib was enhanced by its combination with rituximab or ofatumumab. Moreover, CD20 mAbs and BAKi induced the death of leukaemia cells that was significantly potentiated by their combination. Analysis of the enhancement of cell death in these combinations revealed an approximately additive enhancement induced by rituximab or obinutuzumab combined with ibrutinib or idelalisib. Taken together, our data identified negative regulatory effects of CD20 mAbs and their combinations with BAKi on BCR signalling and cell survival in CLL. In conclusion, this study advances our understanding of mechanisms of action of CD20 mAbs as single agents or in combination with BAKi and could inform on the potential of combined therapies in ongoing and future clinical trials in patients with CLL.